Giuseppe Castiglione (Lang Shining; 1688–1766) and Chinese Painting Tradition: European Approach to the Perspective - Dubrovskaya, Dinara V. (Actual Problems of Theory and History of Art, 2019)
The article deals with several examples of different perspective systems, used by Italian artist Giuseppe Castiglione (Lang Shining), who led a group of court painters at the Manchu court in Beijing, developing the new artistic xianfa method (the linear method). Analysing linear perspective in two hanging and one horizontal (hand-) scrolls, the author demonstrates the artist’s masterly combination of traditional Chinese axonometric depiction with European perspective system while depicting buildings and landscapes, demanded by his royal clients. Touching on the differences between execution and perception of the verticaland horizontal scrolls, the author demonstrates Castiglione’s ability to combine European and Chinese traditional approaches to space delineation, when the artist composes large forms according to the linear perspective principles, and depicts smaller objects using Chinese axonometry. The composition of renowned scroll The Hundred Horses is analysed in detail, being the unique example of surviving Castiglione’s early painting, where the artist unified three perspective vistas with respective vanishing points. The author argues that only format, technique, and pictorial motifs of this work connect this scroll with Chinese tradition, defining origins of Lang Shining’s reopening Chinese multifocal perspective in the artist’s masterly usage of European theatrical scenography theoreticians’ legacy.
Keywords: Chinese painting; Jesuits in China; Jesuit artists; Giuseppe Castiglione; Lang Shining; linear perspective; Chinese perspective; East meets West